Sex as an important biological variable in biomedical research - Lee, Suk Kyeong (BMB Rep, 2018)
Experimental results obtained from research using only one sex are sometimes extrapolated to both sexes without thorough justification. However, this might cause enormous economic loss and unintended fatalities. Between years 1997 and 2000, the US Food and Drug Administration suspended ten prescription drugs producing severe adverse effects on the market. Eight of the ten drugs caused greater health risks in women. Serious male biases in basic, preclinical, and clinical research were the main reason for the problem. This mini-review will describe why and how funding organizations such as the European Commission, the Canadian Institutes of Health Research, and the US National Institutes of Health have tried to influence researchers to integrate sex/gender not only in clinical research, but also in basic and preclinical research. Editorial policies of prominent journals for sex-specific reporting will also be introduced, and some considerations in integrating sex as a biological variable will be pointed out. To produce precise and reproducible results applicable for both men and women, sex should be considered as an important biological variable from basic and preclinical research.